O efeito do empowerment do consumidor no consumo de informação jornalística pelas novas gerações - Coelho, Magali Moreira (2016)
The present study attempt to find deepen knowledge about the millennium generation and its behavior of consumption of journalistic information. The justification for this research is the falling in the consumption of remunerated journalistic information and the importance that these young people have in defining the pattern of consumer behavior in the nearby future. Descriptions of youth consumption from the American Press Institute and Pew Research Center show that young Americans become more active in news consumption. The deepening in the Brazilian universe of consumption of journalistic information sought to describe the behavioral profile of the youth of the generation denominated by some as 'millennium'. In addition, it describes the motivational behavior agents of these young people and similarities. The field survey interviewed 17 young people between 18 and 34 years of age and secondary data were collected in reports and news from newspapers and magazines. The results show that young consumers of journalistic information gain autonomy, choose what they want to read, when and how much they want to read within a wide range of content and sources available in the online world. They are critical of the excess content available, they want information faster, and their main means of access to news is social media, either by sharing between friends on the network or by customizing the information on their Facebook schedule generated by the curation of the platform. Sharing information gives prominence to shared content and its messengers, but does not generate content engagement. The young people interviewed do not want to expose themselves by commenting or discussing the news. This scenario reinforces the idea that has gained prominence in world discussions, on the responsibility of platforms such as Facebook to inform the population as a whole, but especially those young people who do not look for other sources of information to form their opinions.